2020
DOI: 10.1111/bju.15229
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic hyperplasia – what do we know?

Abstract: Objectives To present historical and contemporary hypotheses on the pathogenesis of benign prostatic hyperplasia (BPH), and the potential implications for current medical therapies. Methods The literature on BPH was reviewed. BPH is a prevalent disease with significant health and economic impacts on patients and health organisations across the world, whilst the cause/initiation of the disease process has still not been fully determined. Results In BPH, pathways involving androgens, oestrogens, insulin, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 77 publications
0
123
0
Order By: Relevance
“…It was observed that prostatic hyperplasia was accompanied and/or preceded by a background of inflammatory status. Studies on the pathophysiology of BPH highlighted a significant role for inflammation and inflammatory mediators ( McClinton et al, 1990 ; Theyer et al, 1992 ; Madersbacher et al, 2019 ; Devlin et al, 2020 ). In particular, inflammation was reported to be a key-player in testosterone-induced BPH ( Rastrelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that prostatic hyperplasia was accompanied and/or preceded by a background of inflammatory status. Studies on the pathophysiology of BPH highlighted a significant role for inflammation and inflammatory mediators ( McClinton et al, 1990 ; Theyer et al, 1992 ; Madersbacher et al, 2019 ; Devlin et al, 2020 ). In particular, inflammation was reported to be a key-player in testosterone-induced BPH ( Rastrelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevation in serum testosterone and insulin have been suggested to participate in BPH induced by metabolic syndrome ( Muller et al, 2005 ). BPH includes an abnormally enlarged prostate gland that causes problematic symptoms, including: decreased urinary flow and frequency, trouble initiating flow, nocturia and dribbling ( Berry et al, 1984 ; Devlin et al, 2020 ). Unfortunately, the histological prevalence of BPH at autopsy is believed to be as high as 50%–60% for men in their 60’s, and up to 80%–90% of those over 70 years of age ( Ng and Baradhi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, a cross-sectional survey in six European countries revealed that the mean one-year treatment costs were €858 per patient, three quarters of which concerned medication costs (van Exel et al, 2006). In 2006, UK spent £44 million on primary care, £69 million on drug treatment, and £101 million for treating BPH associated complications, such as AUR (Devlin et al, 2020). In 2019, an estimate based on a cost and treatment pattern reflective of USA Medicare costs reported that the global medical service costs of BPH reached $73.8 billion annually (Launer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathophysiology genesis mechanisms of benign prostatic hyperplasia and prostate cancer have not yet been fully elucidated [1][2][3][4][5]. Men's age is clearly the strongest risk factor [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%